2018
DOI: 10.1016/j.cattod.2016.12.014
|View full text |Cite
|
Sign up to set email alerts
|

Propane oxidative dehydrogenation over VOx/SBA-15 catalysts

Abstract: VO x /SBA-15 catalysts with five different vanadium loadings were prepared by a modified wet impregnation method, characterized using N 2 adsorption, XRD, EDX, SEM, Raman and UV-vis spectroscopies and H 2 -TPR techniques, and tested in the oxidative dehydrogenation of propane in the temperature range 450-600 • C. For all the catalysts the propane conversion increases with both reaction temperature and vanadium loading, while the selectivity for propene decreases mainly to the benefit of carbon oxides. Several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 46 publications
3
33
0
Order By: Relevance
“…1035 cm −1 assigned to the VO stretching mode of tetrahedral vanadate species. 12,20,27,78,79 Although the band observed around 1036 cm −1 is usually associated with the VO vibration of monomeric vanadate species, it would not be theoretically correct to exclude the possibility of the existence of polymeric vanadate species which may have VO vibration bands in close proximity. Thus, it can be suggested that the vanadium sites of the pristine catalyst mainly consist of V 2 O 5 nanocrystals and tetrahedral vanadate species.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…1035 cm −1 assigned to the VO stretching mode of tetrahedral vanadate species. 12,20,27,78,79 Although the band observed around 1036 cm −1 is usually associated with the VO vibration of monomeric vanadate species, it would not be theoretically correct to exclude the possibility of the existence of polymeric vanadate species which may have VO vibration bands in close proximity. Thus, it can be suggested that the vanadium sites of the pristine catalyst mainly consist of V 2 O 5 nanocrystals and tetrahedral vanadate species.…”
Section: Catalysis Science and Technology Papermentioning
confidence: 99%
“…Vanadium, as a cost-effective and environmentally friendly metal, is an attractive alternative catalyst for PDH [7]. Although vanadium catalysts are mainly applied in the oxidative dehydrogenation of propane, researchers have found that they also displayed excellent catalytic performance and high stability for PDH [8,9]. For instance, Gong et al found that VO x /Al 2 O 3 catalysts prepared by the incipient wetness impregnation (IWI) method exhibited extremely high selectivity for propylene (80%) with 35% conversion of propane [5].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of oxidative conversion of propane-butane mixture on various types of catalysts is possible to obtain a range of products such as oxygenates [2][3][4][5] , olefins [6][7][8][9] , hydrogen 10,11 , synthesis gas [12][13][14] and CO 2 + H 2 O 15 .…”
Section: Introductionmentioning
confidence: 99%